PENANGGULANGAN POTENSI RADIKALISME MELALUI PENILAIAN BUKU PENDIDIKAN AGAMA PADA SEKOLAH DAN MADRASAH - Mulyawan Safwandy Nugraha; Mohammad Fauzan (Tatar Pasundan : Jurnal Diklat Keagamaan, 2020)
This research aims to find out: (1) the urgency of religious literature on religious understanding’s development; (2) potential radicalism presented in religious education books both in schools and madaris (3) countermeasure of potential radicalism through evaluating religious education books assessed by the Ministry of Religious Affairs (MORA). The study uses a qualitative descriptive approach with interviews, observation, and documentation studies as the data-gathering tool. In data analysis, researcher uses interactive model involving data reduction, data serving, data display, and conclusion drawing/verifiying. The research findings yield the evaluation policy in the books emerges various cases of religious textbooks, while the various researches and developments findings relate to educational textbooks. Other findings responsed to the law implementation number 3 year 2017 about book matters’ system, Government Regulation number 75 year 2019 on Law Enforcement Regulation, and Minister of Religious Affairs Regulation number 9 year 2018 about religious books evaluation. Quick, precise, and accurate innovation on the evaluation is highly recommended, and technology as well as application is way to solve the problems. Hence, the regulation about religious education book should be immediately issued.  It is also required (special) institutions whose duties and functions are specific to writing, evaluation, and publication in terms of religious educational books (at least equivalent to the first echelon). MORA is expected to charge the issuer openly and transparently as a form of public service with measurable SOP and targets, so that all community guidances of religions could create their respective guidelines on writing and publication.Keywords: radicalism; evaluation; religious education book; MORA